2015
DOI: 10.3141/2519-12
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Most Suitable Pedestrian Level of Service Method for Dhaka City, Bangladesh, through a Synthesis of Measurements

Abstract: In this paper, five pedestrian level of service (PLOS) methods are outlined in brief with respect to their assets and their limitations: (a) the Australian method, (b) the Highway Capacity Manual 2010 method, (c) the trip quality method, (d) the Landis method, and (e) the Tan Dandan method. In this study, each method was implemented to consider its suitability for use in Dhaka City, Bangladesh, through the integration of objective measurement and subjective assessment. The objective measurement consisted of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Thus, environmental stimuli influence the decision of using certain infrastructure or avoiding it entirely. However in the past, it was found that there is low correlation between the SPI perceived by users and that which is estimated by using measurable attributes in-situ (47,48). In an attempt to fill this gap, Ferna´ndez-Heredia et al suggested that including user perceptions to mode choice models could improve their performance (49).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, environmental stimuli influence the decision of using certain infrastructure or avoiding it entirely. However in the past, it was found that there is low correlation between the SPI perceived by users and that which is estimated by using measurable attributes in-situ (47,48). In an attempt to fill this gap, Ferna´ndez-Heredia et al suggested that including user perceptions to mode choice models could improve their performance (49).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among them, 31% of the pedestrian causalities occurred while crossing a road [2]. In addition, the roadway environment of Dhaka is not pedestrian-friendly because of the lack of pedestrian facilities, faulty design, and improper maintenance [3]. Rahman and Khadem conducted a study on the physical and operational deficiency of signal system of Dhaka.…”
Section: Introductionmentioning
confidence: 99%